2020
DOI: 10.3390/ijms21041416
|View full text |Cite
|
Sign up to set email alerts
|

Brain Metastases in Lung Cancers with Emerging Targetable Fusion Drivers

Abstract: The management of non-small cell lung cancer (NSCLC) has transformed with the discovery of therapeutically tractable oncogenic drivers. In addition to activating driver mutations, gene fusions or rearrangements form a unique sub-class, with anaplastic lymphoma kinase (ALK) and c-ros oncogene 1 (ROS1) targeted agents approved as the standard of care in the first-line setting for advanced disease. There are a number of emerging fusion drivers, however, including neurotrophin kinase (NTRK), rearrangement during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 96 publications
1
16
0
1
Order By: Relevance
“…Similarly, a previous study based on SEER database demonstrated that more than half of patients showed bone metastasis within metastatic NSCLC patients 27 . Remarkably, we found that different subtypes showed difference among diverse ECM sites, which is probably because different subtypes have different genetic variation propensities, such as EGFR, ALK, and MET were seen more mutated in AD, while FGFR1 and FGFR3 mutation were more frequent in SCC 28–32 . Indeed, different mutational profiles being prone to distinctive metastatic patterns in lung cancer have been elucidated.…”
Section: Discussionsupporting
confidence: 70%
“…Similarly, a previous study based on SEER database demonstrated that more than half of patients showed bone metastasis within metastatic NSCLC patients 27 . Remarkably, we found that different subtypes showed difference among diverse ECM sites, which is probably because different subtypes have different genetic variation propensities, such as EGFR, ALK, and MET were seen more mutated in AD, while FGFR1 and FGFR3 mutation were more frequent in SCC 28–32 . Indeed, different mutational profiles being prone to distinctive metastatic patterns in lung cancer have been elucidated.…”
Section: Discussionsupporting
confidence: 70%
“…Future clinical trials of the existing selective drugs should aim to differentiate histologies, earlier testing and initiation of treatment during the disease course might increase the number of eligible patients [95]. Moreover, as discussed in the previous section, further clinical trials of drugs, registries and collaborative studies are encouraged to study the efficacy of combinations of RET inhibitors with other targeted agents are advocated to include baseline and serial brain imaging in patients to characterize baseline intracranial disease, response to therapy, and patterns of disease progression [52,96]. We are on the threshold of a new era in targeting RET fusion-positive NSCLCs.…”
Section: Future Perspectives On Drugs and Clinical Trialsmentioning
confidence: 99%
“…Lung cancer is associated with a high rate of central nervous system (CNS) metastases [15][16][17]. ALK rearrangement-positive (ALK-p) NSCLC has been reported to exhibit a high frequency of CNS metastases, which is associated with worse prognosis and reduced quality of life (QOL) [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…A remarkable feature of lorlatinib is that it is designed to cross the blood-brain barrier. This makes it highly effective for the treatment of ALK-p advanced NSCLCs, even those with CNS metastases [16,[28][29][30]. Several in vivo studies have reported that lorlatinib reduces the size of NSCLC brain metastases in mouse models in a concentration-dependent manner [31,32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation